Feeling the field: Reflections on embodiment within improvised dance ethnography. (1st December 2019) - Martin, Rose
AbstractThis article shares methodological meanderings that sit at the intersection of embodiment and improvised dance ethnography. Comprised of a series of personal reflections on fieldwork, the query of 'how does ethnography feel for the researcher?' is explored. While questions pertaining to feelings researchers encounter in the field have been probed with some depth in existing literature, these are not always connected to how the feelings of the researcher are embodied at a somatic level. Through sharing two narratives of challenging moments I have confronted in fieldwork, ideas around notions of embodiment, performing and fear, and violence and vulnerability are illuminated. Through unpacking how improvisational ethnography plays out from an embodied place, from my lived experiences as a dance researcher, there is the potential for fostering a more fully developed somatic understanding of ethnographic dance research as a practice.